Inclusive innovations as a driver of the development of the insurance market of Ukraine (Economics and region, 2025)
The article studies inclusive innovations as a key driver of the development of the insurance market of Ukraine. It is determined that innovations not only contribute to increasing the efficiency of insurance companies but also provide equal access to insurance services for different segments of the population, which is an important factor for the development of financial inclusion. Inclusive innovation allows for the creation of new products and services available to low-income populations, which contributes to social justice and economic growth. It has been established that effective marketing communication is an important factor in the successful implementation of inclusive initiatives. This involves the use of adapted strategies that consider the needs of different populations, personalization of offers and integrated marketing communications (IMC), which ensure a clear and understandable delivery of information to potential customers. Research analysis has shown that properly measuring the effectiveness of marketing campaigns is an important tool for optimizing marketing efforts. This allows you to increase the level of financial inclusion, improve the customer experience, and ensure that offers are more accurately matched to market demands. Digital technologies, which are actively being introduced in the industry, make it possible to simplify insurance processes, make them more convenient and accessible to customers. Cooperation with public organizations and other social institutions also plays an important role, as it contributes to increasing the social responsibility of business and increasing trust in insurance companies. Thanks to such innovations, a more transparent and fairer environment is created for the development of the insurance market, which, in turn, opens new opportunities for business and improves its social image. Thus, inclusive innovations are not only socially significant, but also cost-effective for insurance companies, as they contribute not only to attracting new customers, but also to strengthening the brand's reputation and increasing its competitiveness in the market.
Keywords: inclusive innovations; insurance market; digital transformation; financial inclusion; underserved populations; socioeconomic development